Graphene‐Based Microwave Metasurfaces and Radio‐Frequency Devices - Jin Zhang (Wiley-VCH, 2021)
Graphene, as a 2D material, has attracted significant attention due to its particular electronic band structure and unique physical properties. Metasurfaces integrated with graphene hold great promise for dynamic manipulation of the electromagnetic waves, where metasurfaces with strong resonances enhance the interaction with incident waves and in turn facilitate a deep modulation through electrical doping of graphene. However, the tunable surface conductivity of graphene is very frequency dependent that makes graphene behave significantly different in THz and microwave band. Due to the novel tuning method of graphene–electrolyte‐based sandwich structures, experimental studies of tunable microwave metadevices have aroused wide interests in the past few years. Herein, the recent progress of graphene‐based microwave metasurfaces and related devices, involved but not limited to tunable absorbers, dynamic beam steering, reconfigurable antennas, and attenuators, are reviewed, enriching the experimental developments of graphene in the microwave region.